Liver Transplantation in Acute-on-Chronic Liver Failure: Excellent Outcome and Difficult Posttransplant Course - Chen, Guang-Hou; Wu, Ruo-Lin; Huang, Fan; Wang, Guo-Bin; Zheng, Mei-Juan; Yu, Xiao-Jun; Wang, Wei; Hou, Liu-Jin; Ye, Zheng-Hui; Zhang, Xing-Hua; Zhao, Hong-Chuan (Frontiers in Surgery, 2022)
Background: Acute-on-chronic liver failure (ACLF) patients have high a mortality in a short period of time. This study aimed to compare the prognosis of transplanted ACLF patients to non-transplanted ACLF patients and decompensated cirrhosis recipients. Methods: Clinical data of 29 transplanted ACLF patients, 312 non-transplanted ACLF patients and 60 transplanted decompensated cirrhosis patients were retrospectively collected. Propensity score matching (PSM) analysis was used to match patients between different groups. Results: After PSM, the 90-day and 1-year survival of transplanted ACLF patients was significantly higher than that of non-transplant controls. Although 90-day survival and 1-year survival of ACLF recipients were similar to that of decompensated cirrhosis controls, ACLF recipients were found to have longer mechanical ventilation, longer intensive care unit (ICU) stay, longer hospital stay, higher incidence of tracheotomy, higher expenses and higher morbidity of complication than matched decompensated cirrhosis controls. 90-day and 1-year survival of transplanted ACLF grade2-3 patients was also significantly higher than that of non-transplanted controls. Conclusions: Liver transplantation can strongly improve the prognosis of ACLF patients. In spite of having more burdens (including longer mechanical ventilation, longer ICU stay, higher incidence of tracheotomy, longer hospital stay, higher hospitalization expenses and higher complication morbidity), ACLF recipients can obtain a similar short-term and long-term survival compared to decompensated cirrhosis recipients. For severe ACLF patients, liver transplantation can also significantly improve their short-term and long-term survival.